Study on Influence of Fluid Parameters on Axial Coupled Vibration of Pipeline Conveying Multiphase Flow - Ming Chen; Jimiao Duan; Dan Shu; Long Huang; Xiaochen Chen (International Journal of Chemical Engineering)
Taking a slurry reservoir-pipeline-valve system as research object, axial dynamic vibrations of pipe system were induced by coupled hydraulic transient due to rapid closure of valve at the end of pipe. The influences of fluid parameters in multiphase flow, including void fraction, density ratio, and elastic modulus ratio between solid phase and liquid phase, on vibration behaviors of pipe system were analyzed. Results of this study show that wave velocities of pressure and stress can be attenuated evidently when void fraction in multiphase fluid is increased appropriately; meanwhile, the amplitudes of pressure fluctuation and pipe vibration are also weakened obviously. With the increase of density ratio between solid phase and liquid phase, the vibrational intension of pipe system becomes stronger and stronger. In this instance, the increments of vibrational energy mainly concentrate in fluid, which leads the pressure energy of fluid to rise up quickly. When elastic modulus ratio between solid phase and liquid phase increases, the total elasticity of fluid decreases gradually. At the same time, both pressure energy of fluid and vibrational intension of pipe are enhanced but the increments are very slight.